Sheria, haki, na wajibu katika serikali ya kijiji : uboreshaji wa serikali za vijiji - Kinemo, R. (Old East Publisher, 2004)
On the rights and responsibilities of leaders and villagers on the improvement of their village councils for the benefit of all.